Taxonomic notes on New Caledonian Malpighiales: Acridocarpus, Crossostylis, Erythroxylum, and Xylosma - Pillon, Yohan (Phytotaxa, 2023)
Taxonomic notes are made on the Malpighiales of New Caledonia. The names Acridocarpus austrocaledonicus Baill. (Malpighiaceae), Crossostylis grandiflora Brongn. & Gris, C. multiflora Brongn. & Gris, C. sebertii Pancher ex Brongn. & Gris (Rhizophoraceae), and Erythroxylum novocaledonicum O.E.Schultz (Erythroxylaceae) are lectotypified. Based on published molecular phylogenetic and morphological evidence, Lasiochlamys Pax & K.Hoffm. is better treated as a synonym of Xylosma G.Forst. (Salicaceae), and five new combinations and one new name are provided to implement this change.